Survival of Patients with Chronic Kidney Disease Treated with Radical Cystectomy and Risk Factors of Glomerular Filtration Rate Loss Following Radical Cystectomy: Two Systematic Reviews and Meta-analyses of Interplay Between Radical Cystectomy and Renal Function - Sari Motlagh, Reza; Ghoreifi, Alireza; Yanagisawa, Takafumi; Kawada, Tatsushi; Kikic, Zeljko; Gill, Inderbir; Daneshmand, Siamak; Djaladat, Hooman; Shariat, Shahrokh F (European urology focus, 2024)
CONTEXT: There is no high-level evidence regarding the risk factors of glomerular filtration rate (GFR) loss following radical cystectomy (RC) and survival outcomes of patients with chronic kidney disease (CKD) undergoing RC. OBJECTIVE: To identify the risk factors of CKD in patients treated with RC for bladder cancer and to assess overall and oncological survival of patients with CKD who underwent RC. EVIDENCE ACQUISITION: According to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement, two systematic reviews were performed for studies published before September 30, 2022, assessing (1) risk factors of renal function (RF) decline following RC and (2) overall and oncological outcomes of CKD patients treated with RC. EVIDENCE SYNTHESIS: A total of 21 and 17 studies were included for qualitative and quantitative syntheses, respectively. The first meta-analysis of ten studies (15 502 patients) identified these factors to be significantly associated with GFR loss following RC: advanced age, lower baseline RF, higher Charlson Comorbidity Index (CCI), diabetes mellitus, hypertension, postoperative hydronephrosis, ureteroenteric stricture, and locally advanced disease (hazard ratios [HRs] 1.03, 1.22, 1.5, 1.27, 1.24, 1.69, 1.92, and 5.13, respectively), while sex, preoperative hydronephrosis, perioperative chemotherapy, and diversion type were not. The second meta-analysis of seven studies (6900 patients) demonstrated significantly worse metastasis-free, cancer-specific, and overall survival in patients with higher CKD stages than in those with lower stages (HRs 1.54, 2.09, and 1.47, respectively). CONCLUSIONS: Current evidence suggests that older age, lower baseline RF, higher CCI, diabetes mellitus, hypertension, postoperative hydronephrosis, ureteroenteric stricture, and locally advanced disease are associated with long-term GFR loss following RC. In addition, patients with higher stages of CKD have worse long-term overall and oncological outcomes following RC. These data may help in counseling and decision-making regarding therapy and preventive measures. PATIENT SUMMARY: Several factors have been identified that can help identify patients at risk for glomerular filtration rate loss after radical cystectomy (RC). Chronic kidney disease is associated with poor cancer- and non-cancer-specific outcomes following RC.
Keywords: cystektomie; Kidney; hypertenze; Glomerular Filtration Rate; Renal Insufficiency, Chronic; diabetes mellitus; lidé; Constriction, Pathologic; chronická renální insuficience; Risk Factors; Hypertension; Hydronephrosis; Urinary Bladder Neoplasms; nádory močového měchýře; rizikové faktory; hydronefróza; Diabetes Mellitus; Cystectomy; ledviny; stenóza; hodnoty glomerulární filtrace; Humans